Utilization of Tea Industrial Waste for Low-Grade Energy Recovery: Optimization of Liquid Oil Production and Its Characterization - I. Kathir; K. Haribabu; Aditya Kumar; S. Kaliappan; Pravin P. Patil; C.Sowmya Dhanalakshmi; P. Madhu; Habtewolde Ababu Birhanu (Advances in Materials Science and Engineering)
Pyrolysis oil, produced from industrial as well as municipal solid wastes through pyrolysis, could be a viable renewable alternative fuel. In this study, abundantly available industrial tea wastes are used to produce liquid oil. Flash pyrolysis experiments on a fluidized bed reactor were performed to analyze pyrolysis characteristics. The study evaluated three important process parameters, that is, pyrolysis temperature (300–500°C), particle size (0.5–1.25 mm), and inert gas flow rate (1.5–2.25 m3/hr). The thermogravimetric analysis of the tea wastes demonstrated that the thermal pyrolysis is possible to produce pyrolysis liquid and value added chemicals. The flash pyrolysis experiment produces maximum of 46.3 wt% liquid oil at the temperature of 400°C, particle size of 1.0 mm, and the sweep flow rate of 1.75 m3/hr. The liquid products were analyzed for its physical and chemical characteristics using Fourier transform infrared spectroscopy (FTIR) and gas chromatography-mass spectroscopy (GC-MS). The heating value of the liquid products showed that it can be used as liquid fuels, and its elements can be used for various industrial applications.